The Great Listener1. Issue 3 (1st September 2016) - Roos, Peter
Abstract : This article is a translation of a story published in Die Zeit, April 27, 2006. It describes the dramatic single session a young woman, Margarethe Walter (married name, Margarethe Lutz), had with Sigmund Freud in 1936, as she told it to the author Peter Roos 70 years later.